AFSR/E - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
AFSR/E (Association for Farming Systems Research and Extension) represents a unique movement of agricultural professionals from five continents and diverse disciplinary and institutional backgrounds. The Association was created to support the...